Drug binding to higher ordered DNA structures: netropsin complexation with a nucleic acid triple helix. - Park, Y W (1992)
We have used a combination of spectroscopic and calorimetric techniques to characterize how netropsin, a ligand that binds in the minor groove of DNA, influences the properties of a DNA triple helix. Specifically, our data allow us to reach the following conclusions: (i) netropsin binds to the triplex without displacing the major-groove-bound third strand; (ii) netropsin binding to the triplex exhibits a lower saturation binding density (7.0 base triplets per netropsin bound) than netropsin binding to the corresponding duplex (5.5 base pairs per netropsin bound); (iii) the netropsin-free and the netropsin-bound triplexes each melt in two well-resolved transitions, initial conversion of the triplex to the duplex state followed by duplex melting to the component single-stranded states; (iv) netropsin remains bound to DNA as the triplex melts to the duplex state; (v) netropsin binding thermally destabilizes the triplex in equilibrium with duplex equilibrium dramatically, while thermally stabilizing the duplex to single-strand equilibrium; (vi) netropsin binding to the triplex is enthalpically 4 times more favorable (more exothermic) than netropsin binding to the corresponding duplex; (vii) netropsin binding to the triplex decreases the cooperativity of the triplex----duplex melting event. These results demonstrate that occupancy of the minor groove of a triplex by a ligand such as netropsin can exert a profound impact on the properties of the host triplex, particularly with regard to the equilibrium in which the third strand is expelled from the major groove. Thus, our results reveal considerable major groove/minor groove crosstalk. Such knowledge may prove of practical importance by providing an approach for modulating the affinity and specificity of major-groove-binding third strands in triplex-forming protocols designed to target specific duplex domains. Fundamentally, our results provide insights into the crosstalk that can result when ligands bind to the two major receptor sites of duplex DNA--namely, the major and minor grooves.